The correlation of gestation period and the weight gain in low-birthweight newborns: the cases in perinatology ward of Regional Public Hospital of Banyumas - Ambarsih,; Solikhah, Umi (Proceedings Series on Health & Medical Sciences, 2020)
The change of birth weight on low birthweight newborns reflects the nutrition condition or baby nutrition and related to the baby's immune system. Besides nutrition, the gestation period also affects weight gain on low birth weight newborns. This research to find out the correlation between the gestation period and weight gain on low birthweight newborns in the Perinatology ward of RSUD (Regional Public Hospital) Banyumas. This was quantitative research using an observational experimental design with the retrospective approach. There were 77 respondents as the samples of this research who were taken using a probability sampling technique of simple random sampling. The results showed that 47 (61%) respondents were male. Most of the mothers or 70 respondents (90.9%) were housewives. Most of them or 26 respondents (33.8%) were Primary School graduates. The results of the linear regression test showed that the significance value on the variable of the gestation period was 0007 (p0.05). There was a correlation between the gestation period and weight gain on low birth weight newborns in the Perinatology ward of RSUD Banyumas.